Strategies for Utilizing Social Capital in the "Sapta Darma" Belief Community Amidst Social Stigma - Ahmad Muthohar Sa’idi; Mintarti Mintarti; Muslihudin Muslihudin (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
The purpose of this research is to examine the strategies for utilizing social capital employed by the "Sapta Darma" Belief Community in maintaining its existence amidst the negative stigma that still persists in society. The legality received in the form of the Constitutional Court's decision No. 97/PUU-XIV/2016 regarding the inclusion of belief adherents in the religion column on ID cards has not fully changed public perception regarding their existence. This research is a qualitative study with data collection methods including observation, in-depth interviews, and documentation. The selection of informants was conducted purposively, specifically targeting the leader and members of the community of practitioners. The number of informants is four, consisting of one man and three women. They are in the age range of 20-70 years. The collected data were analyzed using interactive analysis techniques, which consist of data collection, data condensation, data presentation, and conclusion verification. The research results show that the strategy of utilizing social capital by the followers of the "Sapta Darma" belief is carried out in three ways: first, the practice of "Sapta Darma" teachings as a form of bonding capital that functions to strengthen identity and reinforce internal community relationships. Second, involvement in community activities as a form of bridging capital that opens up spaces for information exchange and embodies the practice of noble teachings in social relations. Third, cooperation with government agencies as a form of linking capital that provides broader access to the public sector and supports the sustainability of the community's existence.